Seroprevalence of IgG specific for dengue virus among adults and children in Santo Domingo, Dominican Republic - Yamashiro, Tetsu; Disla, Mildre; Petit, Angela; Taveras, Delfis; Castro-Bello, Mercedez; Lora-Orste, Miguel; Vardez, Sonia; Cesin, Ana Julia; Garcia, Barbara; Nishizono, Akira (The American journal of tropical medicine and hygiene, 2004)
The seroprevalence of dengue (DEN) virus-specific IgG was determined by enzyme-linked immunosorbent assay among 1,008 adults recruited at blood banks and among 201 children less than 10 years old visiting a hospital in Santo Domingo, Dominican Republic. Most (98%, 987 of 1,008) of the adults and 56% (113 of 201) of the children were positive for DEN virus-specific IgG. Among adults, there were no significant differences in the prevalence by age, sex, and residential area of the participants. Among children, the prevalence of DEN virus-specific IgG increased with age (1-2 years old, 0-5%; 3-6 years old, 25-65%; and >/=7 years old, 76-92%). The prevalence in 50% of those less than one year of age was probably due to maternal antibody transfer. Neutralization tests of adult samples indicate that DEN virus infections with different serotypes have occurred sequentially or simultaneously among the inhabitants of Santo Domingo.